Worthwhile use of travel time and applications in the United Kingdom - Richard Batley; Thijs Dekker; Iven Stead (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This paper outlines the rationale, methodologies, key findings and policy implications of the national Value of Travel Time Savings (VTTS) study conducted in Britain during 2014-15. The study found VTTS varied with distance, trip purpose and mode of travel but not with worthwhile use of travel time. Using two case studies, the paper discusses the approach to implementation of the new VTTS estimates and lessons for other countries.
Keywords: 330; Transportzeit; Urlaubsverhalten; Großbritannien